Energetic and exergetic analyses of a solar powered combined compression-absorption refrigeration system. (31st March 2021) - Khaliq, Abdul; Alharthi, Mathkar A.; Alqaed, Saeed
This study presents a theoretical framework for the thermodynamic analysis of a combined system which can simultaneously produce cooling for both refrigeration (−5°C) and air conditioning (10°C) for the hot climatic regions in an eco-friendly and carbon free manner. A tower solar collector unit was employed to drive the proposed combined cooling system which consists of a hydrocarbon operated vapour compression refrigeration system that is fed by power from steam turbine shaft, and a waste heat operated single-effect LiBr-H2 O operated absorption chiller. A mathematical model using the balances of energy and exergy over the components of the system was developed, and solved using engineering equation solver software. A parametric analysis was conducted to estimate the influence of operating conditions on the system performance. The results show that at baseline operation of the system, for R600a operated VCR, the energetic efficiency of combined system was found to be 73.66% and the exergetic efficiency was 36.43%, while for R290 operated VCR, the energetic and exergetic efficiencies of the combined system were found to be 37.17% and 21.04%, respectively.